Manfaat Channel Youtube Nussa dan Rarra dalam Mengedukasi Anak Usia Dini - Utami, Winda Trimelia; Azizah, Nabila Nurul; Diyaulmuhana, Diyaulmuhana; Fernando, Gabriel Rizky Rahmat (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2022)
There are many ways that can be used as media for educating children from a young age. One of them is to look at the youtube channel that is currently available. The youtube channel of Nussa and Rara is well known in the world of children because it provides content with Islamic values. The purpose of this study is to analyze the values of Islamic education on Nussa and Rara's youtube channels in educating early childhood. This study uses a qualitative method with a content analysis approach. The data source is from one of the films on the Nussa and Rara YouTube channels. The movie consists of 12 episodes with a total duration of 1 hour 11 minutes 33 seconds. In this research, the author uses the thematic method by using Nvivo 12 software as a data analysis method and tool. Overall, the results of the analysis show that there are twelve advantages of Nussa and Rara's YouTube channels in raising young children, including: (i) always remember Allah, (ii) respect parents, (iii) help each other, (iv) sharing, (v) think positively, (vi) be honest, (vii) civilized, (viii) responsibility Â (ix) be patient, (x) be grateful, (xi) apologize, (xii) do not waste. The results of this study can be used as an illustration that can help children in the developmental process and help parents in the selection of programs given to children.